1995
DOI: 10.1128/iai.63.4.1478-1483.1995
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Francisella tularensis LVS in macrophages: the acidic intracellular compartment provides essential iron required for growth

Abstract: Murine macrophages supported exponential intracellular growth of Francisella tularensis LVS in vitro with a doubling time of 4 to 6 h. LVS was internalized and remained in a vacuolar compartment throughout its growth cycle. The importance of endosome acidification to intracellular growth of this bacterium was assessed by treatment of LVS-infected macrophages with several different lysosomotropic agents (chloroquine, NH 4 Cl, and ouabain). Regardless of the agent used or its mechanism of action, macrophages tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(58 citation statements)
references
References 34 publications
3
55
0
Order By: Relevance
“…2); and (iv) survival and multiplication in [5,9,10]. There are many arguments suggesting that the low pH environment within phagosomal compartments of the cell is critical for many intracellular pathogens to access cellular iron for growth [11,12]. CQ treatment of different cells, including macrophages, could inhibit the growth of several of these intracellular bacteria by neutralising the phagolysosomal pH (Table 1; Figs.…”
Section: Cq/hcq Efficacy Against Bacterial Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…2); and (iv) survival and multiplication in [5,9,10]. There are many arguments suggesting that the low pH environment within phagosomal compartments of the cell is critical for many intracellular pathogens to access cellular iron for growth [11,12]. CQ treatment of different cells, including macrophages, could inhibit the growth of several of these intracellular bacteria by neutralising the phagolysosomal pH (Table 1; Figs.…”
Section: Cq/hcq Efficacy Against Bacterial Infectionsmentioning
confidence: 99%
“…palearctica are facultative intracellular bacteria responsible for tularaemia. It has been demonstrated that F. tularensis finds a successful niche for replication in an acidified vacuole where iron is concentrated [12]. Growth of F. tularensis in murine macrophages has been shown to be dramatically inhibited in vitro by CQ in a dose-dependent manner [12].…”
Section: Francisella Tularensismentioning
confidence: 99%
See 1 more Smart Citation
“…Iron acquisition systems also appear to play a key role in promoting the growth of F. tularensis in macrophages (Fortier et al, 1995). Initial studies suggested that acidification of phagosomes was required for the acquisition of iron by F. tularensis (Fortier et al, 1995), but a more recent study has shown that the bacterium blocks phagosome acidification (Clemens et al, 2004). The findings outlined above would indicate that the bacterium must also be able to acquire iron after escape into the cytosol.…”
Section: Virulence Mechanisms Of F Tularensismentioning
confidence: 99%
“…F. tularensis is a faculative intracellular pathogen because it can be cultured in cell-free growth medium as well as inside host cells (Ellis et al ., 2002;Elkins et al ., 2003), but there are no data demonstrating extracellular replication during human or animal infection (Conlan and North, 1992;Fortier et al ., 1994). Thus, F. tularensis may be an obligate intracellular pathogen in vivo , where it has been found to survive and replicate within macrophages, among other cell types (Anthony et al ., 1991;Conlan and North, 1992;Fortier et al ., 1995). Humans can be infected by inhaling as few as 10 F. tularensis , making this one of the most infectious pathogens known (Dennis et al ., 2001;Ellis et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%